Drunken lipid membranes, not drunken SNARE proteins, promote fusion in a model of neurotransmitter release - Coffman, Robert E.; Kraichely, Katelyn N.; Kreutzberger, Alex J. B.; Kiessling, Volker; Tamm, Lukas K.; Woodbury, Dixon J. (Frontiers in Molecular Neuroscience, 2022)
Alcohol affects many neuronal proteins that are upstream or down-stream of synaptic vesicle fusion and neurotransmitter release. Less well studied is alcohol’s effect on the fusion machinery including SNARE proteins and lipid membranes. Using a SNARE-driven fusion assay we show that fusion probability is significantly increased at 0.4% v/v (68 mM) ethanol; but not with methanol up to 10%. Ethanol appears to act directly on membrane lipids since experiments focused on protein properties [circular dichroism spectrometry, site-directed fluorescence interference contrast (sdFLIC) microscopy, and vesicle docking results] showed no significant changes up to 5% ethanol, but a protein-free fusion assay also showed increased lipid membrane fusion rates with 0.4% ethanol. These data show that the effects of high physiological doses of ethanol on SNARE-driven fusion are mediated through ethanol’s interaction with the lipid bilayer of membranes and not SNARE proteins, and that methanol affects lipid membranes and SNARE proteins only at high doses.